2017
DOI: 10.1183/16000617.0097-2016
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term effects of diving on pulmonary function

Abstract: @ERSpublicationsThe effects of diving on pulmonary function largely depend on factors associated with the individual diving response http://ow.ly/aIFS3095WNnCite this article as: Tetzlaff K, Thomas PS. Short-and long-term effects of diving on pulmonary function. ABSTRACT The diving environment provides a challenge to the lung, including exposure to high ambient pressure, altered gas characteristics and cardiovascular effects on the pulmonary circulation. Several factors associated with diving affect pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 64 publications
1
33
0
5
Order By: Relevance
“…In the most recent studies, FCV has been shown to increase significantly after 3 or more years of professional diving [7,11,19]. Although the oldest studies showed a reduction, it is generally accepted that VC and FVC increase due to the divers' training [1,18]. For this study, there was no connection with physical activity in general or with diving.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…In the most recent studies, FCV has been shown to increase significantly after 3 or more years of professional diving [7,11,19]. Although the oldest studies showed a reduction, it is generally accepted that VC and FVC increase due to the divers' training [1,18]. For this study, there was no connection with physical activity in general or with diving.…”
Section: Discussionmentioning
confidence: 67%
“…Since our subjects had no other professional toxic exposure, we may conclude that this flow reduction derives from the diving experience, suggesting an effect on first the bronchioles and then the larger bronchi. The hypothesis of small airways disease in professional divers has been discussed for several decades [1]. Some studies have shown the appearance Richard Pougnet et al, Evolution of the respiratory function of professional divers over 15 years of small airways disease among recreational divers [22], but these results have not been systematically shown in all studies for professional divers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(p=0,569) Katılımcıların dalış bilgileri Tablo 1'de verilmiştir. Gün 1 4,34±0,84 4,44±0,81 1,000 5,18±1,04 5,43±1,02 0,087 0,83±0,13 0,82±0,08 1,000 Gün 2 4,39±0,78 4,37±0,85 1,000 5,21±0,97 5,28±1,06 1,000 0,85±0,07 0,83±0,09 1,000 Gün 3 4,27±0,82 4,29±0,87 1,000 5,16±1,03 5,18±1,10 1,000 0,83±0,08 0,84±0,09 1,000 Gün 4 4,28±0,86 4,28±0,82 1,000 5,21±1,02 5,24±1,03 1,000 0,83±0,09 0,82±0,08 1,000 Gün 5 4,26±0,89 4,25±0,85 1,000 5,17±1,07 5,18±1,01 1,000 0,81±0,13 0,82±0,08 1,000 (Tetzlaff, Thomas, 2017). Direncin artmasına bir sebep de regülatörün kendisidir.…”
Section: Bulgularunclassified